2023
DOI: 10.1007/s10880-023-09937-5
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Impact of Covid-19-Related Perceptions on Psychological Distress and Quality of Life in an International Gastrointestinal Cohort Over Time Guided by the Common Sense Model

Abstract: The aim of this longitudinal study was to examine changes in COVID-19 and illness-related perceptions, gastrointestinal symptoms, coping, catastrophising, psychological distress, and QoL during the COVID-19 pandemic. A total of 831 adults with a gastrointestinal condition completed an online questionnaire at baseline (May—October 2020). Of those, 270 (32.5%) participants (85.2% female, mean age = 47.3 years) provided follow-up data (March—May 2021). Repeated-measures multiple analysis of variance and a cross-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 70 publications
0
0
0
Order By: Relevance
“…Furthermore, a recent retrospective biobank cohort study (N = 65, 421) revealed that individuals living with both endometriosis and IBS are more likely to suffer from multiple co-occurring conditions and experience greater abdominal and pelvic pain compared to individuals with endometriosis or IBS alone [57]. In endometriosis and IBS, disease-related pain is signi cantly associated with increased symptoms of depression and anxiety, pain catastrophising and fatigue [35,37,40,[71][72][73], whilst disease severity may directly in uence how individuals with IBS adaptively cope with and respond to pain [74][75][76]. Accordingly, the presence of comorbid IBS-type symptoms in endometriosis potentially in uences individual responses to condition-related factors and may exacerbate adverse health outcomes, impairing overall HRQoL.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a recent retrospective biobank cohort study (N = 65, 421) revealed that individuals living with both endometriosis and IBS are more likely to suffer from multiple co-occurring conditions and experience greater abdominal and pelvic pain compared to individuals with endometriosis or IBS alone [57]. In endometriosis and IBS, disease-related pain is signi cantly associated with increased symptoms of depression and anxiety, pain catastrophising and fatigue [35,37,40,[71][72][73], whilst disease severity may directly in uence how individuals with IBS adaptively cope with and respond to pain [74][75][76]. Accordingly, the presence of comorbid IBS-type symptoms in endometriosis potentially in uences individual responses to condition-related factors and may exacerbate adverse health outcomes, impairing overall HRQoL.…”
Section: Discussionmentioning
confidence: 99%